Desafíos de la colaboración digital entre museos etnológicos y comunidades indígenas: dos perspectivas, una conclusión - Andrea Scholz; Mirῖgõ-Diana Guzmán Ocampo (Journal de la Société des Américanistes)
Digital platforms offer many opportunities for the opening and transcultural exploration of museum collections. From 2015 to 2021, the project “Sharing Knowledge” at the Ethnological Museum of Berlin has been meeting the challenges associated with this new field of collaborative work. Experience gained together with indigenous partners from Latin America shows that the creation of new knowledge infrastructures requires a major rethink. It is not enough to open up the collections to the perspectives of others. Successful digital collaboration must reflect the heterogeneous infrastructures of knowledge of those involved.